Management einer chronischen vorderen, verhakten Schulterluxation während des COVID-19-Lockdowns - Tenfelde, Oliver (Arthroskopie, 2021)
This article describes the case of a chronically dislocated anterior shoulder in a 25-year-old mentally retarded patient, who received delayed orthopedic specialist care during the first COVID-19 lockdown. The therapy consisted of open reduction using lesser tuberosity osteotomy, filling of the Hill-Sachs defect and anterior glenoid augmentation, each with autologous tricortical bone graft of the iliac crest. While this injury is rare in countries with an advanced healthcare system, studies from countries with limited access to healthcare show a higher incidence, often with higher-grade functional impairment.